Ethics and social responsibility in practice: interpreters and translators engaging with and beyond the professions. (3rd April 2017) - Drugan, Joanna
ABSTRACT: Interpreting and translation are unregulated activities in most countries, yet interpreters and translators perform challenging work in sensitive domains, such as the law, medicine and social work. Other professionals working in these sectors must complete formal ethics training to qualify, then subscribe to Codes of Practice or Ethics. When they face ethical challenges in their work, they can access ongoing support. They must undertake regular refresher training in ethics. Interpreters and translators rarely have access to this sort of ethical infrastructure. This places the onus on interpreters and translators to reflect on ethical aspects of their practice, for reasons related to both professional performance and social responsibility. This contribution presents original UK-based research with one type of professional 'clients' who rely on interpreters and translators, social workers and social work students prior to their first work experience placement. Findings suggest that insufficient attention has been paid to such professional clients and that ethical aspects of professional communication can be compromised as a result. By framing ethics training and ongoing support in terms of social responsibility, we point to some ways in which the different professional groups might communicate and work more effectively with one another and with service users.